Paths from Proactive Personality and Family Influence to Employability - Sawitri, Dian Ratna; Ratnaningsih, Ika Zenita (SCAD Independent, 2020)
Employability has become an increasingly relevant construct in modern turbulent world economic markets especially in this industrial revolution 4.0 era. Perceived employability involves self-perceived ability to achieve sustainable employment appropriate to one’s level of qualifications. Individual and family-related variables have been identified as predictors of employability in undergraduate students. However, the roles of career action behaviors of planning the future career and exploration of the world of work in these relationships are rarely known. This study aimed to examine the paths from proactive personality and family influence to employability via career planning and exploration. We collected data from 321 undergraduate students from a university in Semarang, Indonesia, M age = 19.89 years, SD age = 5.39, 67.3% female. We used scales of proactive personality, family influence, career planning, career exploration, and employability to collect the data. Structural equation modeling showed that the paths from proactive personality and family influence to employability were all partially mediated by career planning and exploration. Our results underlined the roles of career planning and exploration as mechanisms by which proactive personality and family influence exerted their influences on employability in undergraduate students. The recommendations of the findings of this study are discussed.